(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Hepatitis C virus (HCV) treatment reduces hepatic and extrahepatic morbidity and mortality and prevents further transmissions. Since October 2017, direct-acting antivirals (DAAs) have been reimbursed in Switzerland for all patients. Intravenous drug use accounts for the majority of HCV infections in Switzerland. Between July 2013 and July 2015, 205 of the 631 opioid agonist therapy (OAT) patients in the Swiss canton Aargau were enrolled into a cohort study, the Argovian OAT cohort study. In March 2019, the Federal Office of Public Health (FOPH) published guidelines for the HCV management in drug users. AIM To describe current HCV management in OAT patients of the Swiss canton Aargau in view of the FOPH guidelines and to compare the management of patients within and outside the cohort study. METHODS Between July 2013 and August 2018, 330 patients were enrolled into the Argovian OAT cohort study offering human immunodeficiency virus (HIV)/HCV antibody rapid testing, noninvasive liver fibrosis assessment (Fibroscan®) and, since August 2017, capillary HCV RNA rapid testing with the GeneXpert®. To assess HCV management, all information available before 1 September 2018 was considered. In September 2018, 592 of the then 809 OAT patients were not yet enrolled into the cohort study. For them, the cantonal physician sent a questionnaire regarding HCV, HIV, and hepatitis A and B viruses (HAV and HBV) to the OAT prescriber. Up to September 2019, we had received 182 (31%) questionnaires; 160 were eligible for analysis. RESULTS In the HCV cascade, the four diagnostic gaps, but not the two treatment-related gaps, were significantly larger in non-cohort compared with cohort patients: (1) never HCV antibody screened: 14% (22/160) versus 0.3% (1/330); (2) no HCV RNA test, if HCV antibody positive: 36% (21/58) versus 11% (19/167) if ever chronically infected; (3) liver fibrosis stage unknown: 51% (19/37) versus 3% (4/120); (4) HCV genotype unknown: 41% (15/37) versus 18% (21/120); (5) never received HCV treatment: 24% (9/37) versus 30% (36/120); (6) no treatment success, if treated and outcome known: 7% (1/14) versus 6% (5/84). HCV treatment outcome was unknown by the OAT prescriber in 50% of non-cohort patients. Adequate HCV management (HCV antibody test ≤1 year ago if HCV antibody negative or last HCV RNA test negative, and ≤1 year ago if HCV antibody positive) was less frequent in non-cohort than in cohort patients: 28% (44/160) versus 69% (229/330). CONCLUSION With regard to HCV elimination in OAT patients by 2030, case finding and regular screening for new and re-infections remain a challenge, especially for non-cohort patients in a decentralised setting. Documentation of the HCV sero- and RNA status of each OAT patient by the cantonal physician and a yearly HCV screening reminder sent to the OAT prescriber combined with capillary HCV antibody and HCV RNA testing by the OAT prescriber, general practitioner or the pharmacy might facilitate the implementation of the FOPH guidelines. DAA prescription directly by the OAT prescriber could increase awareness and improve linkage to care.